Energy Relations between Turkey and Russia: Conflict In Energy Projects - Yavuz Tiftikçigil, Burcu; YESEVİ, ÇAĞLA GÜL (My University, 2014)
Energy is the most strategic sector which necessitates long term decisions that highly affect the economy, development, internal security and foreign policy of a country. Continuing significance of oil and gas in geopolitics affects the positions and strategies of actors. The Middle East and Eurasia controls the most a significant portion of hydrocarbons that are yet to be discovered. Russia holds the world's largest natural gas reserves, the second-largest coal reserves, and the ninth-largest crude oil reserves. Turkey has concentrated its efforts for the transportation of Caspian oil and gas reserves to Western markets on the realization of the EastWest Energy Corridor, and North-South Corridor. Turkey will inevitably contribute to Europe’s energy supply security. Turkey’s objective is to become Europe’s fourth main artery of energy supply. New pipelines will enhance Turkey’s role as an important transit country on the Eurasia energy axis and energy hub in the region. In this study, the history of Turkish and Russian energy policies and main principles of their energy strategies. Main aim of this study is to investigate Russian-Turkish energy cooperation and conflictual energy projects.
Keywords: Energy; Security of energy supply; Enery co-operation; Energy Policies